Psychosocial factors associated with the assessment of testimony credibility in Child Sexual Abuse - Cabezas-García, María; de la Peña Fernández, María Elena; Andreu Rodríguez, José Manuel (Anales de Psicología / Annals of Psychology, 2022)
Background: Credibility assessment in Child Sexual Abuse (CSA) poses a major challenge for forensic psychology. The lack of evidence supporting the determination of the real occurrence of the abuse requires additional approaches to assess credibility. The purpose of this research is to explore the existence of psychosocial factors associated with testimony credibility in CSA. Method: Ninety-nine CSA cases characterized as Credible (C) or Not Credible (NC) were evaluated. The age range of the group spanned 4 to 17 years (M = 11.31, SD = 3.92) with 87 (85.9%) cases corresponding to females. Group C incuded 68 cases and NC group the remaining 31. The relationship between the expert opinion (C/NC) and psychosocial factors was evaluated using contingency tables and chi-square analysis. Results: Significant differences in variables such as the presence of sexual and emotional imbalances, dysfunctional family dynamics, parent litigation, or legal actions against a relative were found. Conclusions: Certain variables were commonly present in the NC group, such as symptoms of a sexual nature, dysfunctional familiar dynamics, divorced parents, presence of litigation between parents, or legal actions against the biological father.